A destinação de fármacos e medicamentos vencidos na perspectiva da legislação: um estudo dos municípios do Oeste do Paraná - Oliveira, Clarice Rodrigues de (2022)
Expired drugs and medicines, when disposed of irregularly, end up causing various environmental issues, such as contamination of the soil, surface, and groundwater, as well as health problems for the population that ends up having to rely on these substances, as some are resistant and are not completely removed in water or sewage treatment plants. In this way, this work aims to evaluate the existence of legislation at the Federal, State, and Municipal levels, which points to the proper disposal and disposal of this waste. The Federal Constitution of Brazil provides that it is the duty of the Municipalities, States, and Unions to seek ways to solve, as well as to create measures that make it possible to improve or prevent environmental problems, thus ensuring that future generations can also enjoy an ecologically balanced environment. In this way, to solve the guiding question of the present research, the general objective was delimited through documental research and bibliographic review, to verify the existence, of laws; bills, and administrative requirements aimed at the control of pharmaceuticals and drugs at the national level; state and municipalities in western Paraná with more than 50,000 (fifty thousand) inhabitants. It was found that at the federal level there is legislation that shows the way to be followed by the States in the face of solid waste and reverse logistics, the State, in turn, seeks to hold manufacturers and suppliers responsible for the correct disposal via reverse logistics. Finally, only the municipality of Foz do Iguaçu, Cascavel has a current law for the collection of expired medicines, Medianeira has in its Director Plan the application of reverse logistics, and the municipality of Marechal Cândido Rondon, has only a bill and requirements, e, Toledo no search results were returned. Therefore, it shows the importance of working on legislation directly aimed at drugs and medicines, as well as public policies regarding the population's awareness, disposal, and destination of this waste.